Humanistic Pedagogy Across the Disciplines Approaches to Mass Atrocity Education in the Community College Context (Springer International Publishing, 2018)
This volume presents insights from five years of intensive Holocaust, genocide, and mass atrocity education at Queensborough Community College (QCC) of the City University of New York (CUNY), USA, to offer four approaches-Arts-Based, Textual, Outcomes-Based, and Social Justice-to designing innovative, integrative, and differentiated pedagogies for today's college students. The authors cover the theoretical foundations of each approach, and include faculty reflections on the programs, instructional strategies, and student reactions that brought the approaches to life across the disciplines.